Interstitial pneumonia with autoimmune features and platypnea-orthopnea syndrome. Issue 9 (6th September 2019) - Mathew, Uthara; Mittal, Ankit; Vyas, Surabhi; Ray, Animesh
Abstract : Interstitial pneumonia with autoimmune features (IPAF) is a recently proposed terminology for interstitial lung disease (ILD) with evidence of autoimmunity that does not meet the criteria for a defined connective tissue disease (CTD). Although ILD is well recognised in patients with established CTD, it is rarely the sole presenting feature of CTD. We report a case of 22-year-old male patient, who presented with progressive shortness of breath for 2 months and had features suggestive of platypnea-orthodeoxia syndrome (POS). Imaging revealed ILD with usual interstitial pneumonia pattern. Patient had features of autoimmune disorder but did not fulfil the criteria for any CTD and hence was labelled as IPAF. His POS was attributed predominantly to the lower lobe disease. The patient responded well to immunosuppressive treatment. A systematic review of literature of all cases with POS due to pulmonary parenchymal involvement has also been done.